Association between pre-infarction angina and culprit-lesion morphology in patients with ST-segment elevation myocardial infarction: an optical coherence tomography study. (25th November 2020) - Wang, Y; Sheng, Z; Li, J; Tan, Y; Zhou, P; Liu, C; Zhao, X; Zhou, J; Chen, R; Song, L; Zhao, H; Yan, H
Abstract: Background: Previous studies reported the cardiac protection effect of pre-infarction angina (PIA) in patients with acute myocardial infarction (AMI). However, the association between PIA and culprit plaques characteristics in AMI patients through optical coherence tomography (OCT)assessment remains unclear. Purpose: We sought to identify culprit-plaque morphology associated with PIA in patients with ST-segment elevation myocardial infarction (STEMI) using OCT. Methods: A total of 279 STEMI patients who underwent intravascular OCT of culprit-lesion were included. Baseline clinical data and culprit-plaque characteristics were compared between the PIA group the non-PIA group. Results: Patients with PIA represented 54.8% of the study population (153 patients). No differences were observed in clinical and angiographic data between two groups, except STEMI onset with exertion was significantly less common in PIA group (24.2% versus 40.5%, P=0.004). Patients with PIA exhibited a significantly lower incidence of plaque rupture (40.5% versus 61.9%, P<0.001) and lipid-rich plaques (48.4% versus 69.0%, P=0.001). The thin-cap fibroatheroma (TCFA) prevalence was lower in PIA group, presenting a thicker fibrous cap thickness, although statistically significant differences were not observed (20.3% versus 30.2%, P=0.070; 129.1±92.0μm versus 111.4±78.1μm, P=0.088; respectively). Multivariate logistic regression analysis indicated that PIA was an independent negative predictor for plaque rupture (odds ratio: 0.44, 95% confidence interval: 0.268–0.725, P=0.001). Conclusion: STEMI patients with PIA showed a significantly lower prevalence of plaque rupture and lipid-rich plaques in culprit-lesion than non-PIA group, implying different mechanisms of STEMI attack. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Association between pre-infarction angina and culprit-lesion morphology in patients with ST-segment elevation myocardial infarction: An optical coherence tomography study